2019
DOI: 10.1530/rep-18-0530
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 at the crossroads of corpus luteum fate decisions

Abstract: The multimodular matricellular protein thrombospondin-1 (THBS1) was among the first identified endogenous antiangiogenic molecules. Recent studies have shown THBS1-mediated suppression of angiogenesis and other critical activities for corpus luteum (CL) regression. THBS1 is specifically induced by prostaglandin F2alpha in mature CL undergoing regression, whereas luteinizing signals such as luteinizing hormone and insulin reduced its expression. THBS1 interacts both synergistically and antagonistically with oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 106 publications
(130 reference statements)
5
24
0
Order By: Relevance
“…Indeed, we have previously demonstrated that tumor necrosis factor-α anti-angiogenic role comprised TSP1 and its receptor CD36 activation in equine luteal cells (16). Furthermore, in bovine CL, PGF 2α induced-luteolysis mediated the upregulation of TSP1 and CD36 (10, 13, 36, 37), a finding which is in agreement with our former results. In the present study, we reported the upregulation of TSP1 and CD36 by Nodal in in vitro explants of equine mid CL.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Indeed, we have previously demonstrated that tumor necrosis factor-α anti-angiogenic role comprised TSP1 and its receptor CD36 activation in equine luteal cells (16). Furthermore, in bovine CL, PGF 2α induced-luteolysis mediated the upregulation of TSP1 and CD36 (10, 13, 36, 37), a finding which is in agreement with our former results. In the present study, we reported the upregulation of TSP1 and CD36 by Nodal in in vitro explants of equine mid CL.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we used both PGF 2α and LH treatments as a positive controls for our culture system. Expectedly, PGF 2α amplified both TSP1 mRNA and protein and CD36 protein, as seen before in bovine CL (10, 13, 36, 37). However, no changes were seen on CD36 mRNA.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations